Study of underlapped finfets behavior for a radiation sensing purpose - Da Silva Fonseca, Willliam [UNESP]; Agopian, Paula Ghedini Der [UNESP] (The Electrochemical Society, 2020)
In this paper the electrical characteristics of the Underlapped FinFET transistor is studied for different underlap lengths and underlap oxide material. Disturbs caused by underlap region, such as series resistance effect and the spreading electric field have been evaluated. Besides the underlap length, the impact of oxide permittivity on the on-state current level, fringing fields increasing and on current density was also evaluated. When analyzing the Underlapped FinFET as a radiation sensor, the better sensitivity was obtained for long underlap regions and for transistor biased with high drain voltage. The potential increasing in the underlap region results in on-state current enhancement, which characteristic allows this device present good response for sensing purposes.
Keywords: Experimental electrical characterization; Radiation sensors; Underlapped FinFET